The whys and whats of OPERAS - Mounier, Pierre; Aspaas, Per Pippin (Open Science Talk, 2022)
Pierre Mounier presents OPERAS, the European research infrastructure dedicated to open scholarly communication in the social sciences and humanities. With 10 core and a further 40+ member institutions from 16 different countries, its aim is to share knowledge between stakeholders across Europe. As a distributed infrastructure, OPERAS consists of a number of multinational Special Interest Groups that work on specific topics with the aim of developing services and conducting projects at a European level. Ranging from technical service providers and libraries through university presses and learned societies to entire research institutes and universities, OPERAS brings together a variety of stakeholders that work collectively to promote open dissemination of research-based knowledge about society and culture. All interest groups are convened twice a year for an "assembly of the commons"; further coordinating and strategic tasks are taken care of by an Executive Committee and a General Assembly. All member organisations are required to work for open access. Individuals that want to contribute are encouraged to check whether there are any member institutions in their country; in case not, they can always contact one of the coordinators (Pierre Mounier or Suzanne Dumouchel) or another member of the Executive Committee directly. Recording made in conjunction with the 17th Munin Conference on Scholarly Publishing. First published online: December 27, 2022.